Optimization of thin polystyrene waste embedded multiwall carbon nanotubes (MWCNT) film for solid electrolyte of flexible dye-sensitized solar cell (DSSC) - Anuar Abdul Muin, M. (Elsevier Ltd, 2022)
The consumption of organic solvent in a conventional liquid-based electrolyte give rise to the solvent's evaporation, hermetic sealing of the cell as well as lack of cell durability. In order to avoid fluidity and potential leakage, the composite polymer-based electrolyte has been investigated. Thus, the main objective of this study is to develop thin polystyrene waste embedded multiwall carbon nanotube (MWCNT) film with improving electrochemical properties as electrolyte host for flexible DSSC application. In this study, the MWCNT will be functionalized with carboxyl group using sulfonitric solution. Transmission electron microscope (TEM) were used to evaluate the morphology of MWCNT. Different weight percentage of the functionalized MWCNT were embedded into the polystyrene and their effect on the morphology, and uniformity of the thin polymer films were analysed using field emission electron microscope (FESEM). The electrochemical properties of the prepared polystyrene embedded MWCNT based polymer electrolyte were studied using electrochemical impedance spectroscopy (EIS). The finding shows that the optimum loading of MWCNTs in the thin polystyrene waste embedded MWCNTs film is 0.003 g. These composition exhibits the highest ionic conductivity and the lowest resistance. Further increase in the amount of MWCNTs results in reducing the ionic conductivity due to the percolation network of the MWCNT with the polystyrene. Â© 2022